Study of labor utilization and man to machine ratio at automative component company - Nurernie Sabrilna , Maesman (2013)
The effective use of man power is essential in manufacturing industry for high return of investment from expensive resource nowadays. Thus, this study has been carried out as the platform to utilise the resource of the company. The study of labor utilisation and man to machine ratio is about improving productivity through identifying the current labor utilisation before man to machine ratio can be determined using time study methodology. The problem rose from the undefined and unbalance work content lead to this study to utilise the resource of the company. This study has been carried out using time study method and data have been analysing using Tecnornatix Plant Simulation. The objective of the this study are to observe and record the sequence of the task time performed by operator, and analyse the data using the simulation to determine the current labor utilisation of floor console assembly line and propose man to machine ratio for the company. From this study, the utilisation of labor utilisation of each workstation can be determined in order to propose to the management the investigate area for fully use the resource. Operators A in lid console assembly line indicate the labor utilisation of 81.8% that is the highest value of labor utilisation. The current man to machine ratio is 1:1 for all the process. But after the improvement has been made, the line can support 1:2 ratio for process D and process I. The improvement when it implement will enable the company to reduce the operational cost as well as achieve the competitiveness among other competitors.